Аудит систем управління навколишнім середовищем i міжнародні стандарти - Тютюник, Лариса Іванівна; Іванова, Лідія Анатоліївна; Налізко, Олег Володимирович (НТУ "ХПІ", 2008)
Аудит систем управления окружающей средой (СУОС) является открытым для развития методом в рамках более общей СУОС, с помощью которого в стратегию бизнеса и в основные параметры производственного процесса поэтапно внедряются все более жесткие экологические требования. Это инструмент для систематической проверки внутренне фирменного потенциала и рисков. СУОС по международным стандартам ISO серии 14000.

He audit of the control systems by an environment shows itself the opened for development method opened by itself within the framework more general, by which in strategy of business and in the basic parameters of production process stage-by-stage is inculcated all more hard ecological requirements. This is an instrument for systematic verification inwardly brandname potential and risks on the international standards of the ISO series 14000.
Audit of control systems by environment and international standards
Keywords: стратегія бізнесу; екологічні вимоги; управління якістю; природоохоронні заходи